In vivo quantitative magnetization transfer imaging correlates with histology during de‐ and remyelination in cuprizone‐treated mice. (9th January 2015) - Turati, Laura; Moscatelli, Marco; Mastropietro, Alfonso; Dowell, Nicholas G.; Zucca, Ileana; Erbetta, Alessandra; Cordiglieri, Chiara; Brenna, Greta; Bianchi, Beatrice; Mantegazza, Renato; Cercignani, Mara; Baggi, Fulvio; et al.
<x xml:space="preserve">Abstract</x> The pool size ratio measured by quantitative magnetization transfer MRI is hypothesized to closely reflect myelin density, but their relationship has so far been confirmed mostly in ex vivo conditions. We investigate the correspondence between this parameter measured in vivo at 7.0 T, with Black Gold II staining for myelin fibres, and with myelin basic protein and beta‐tubulin immunofluorescence in a hybrid longitudinal study of C57BL/6 and SJL/J mice treated with cuprizone, a neurotoxicant causing relatively selective myelin loss followed by spontaneous remyelination upon treatment suspension. Our results confirm that pool size ratio measurements correlate with myelin content, with the correlation coefficient depending on strain and staining method, and demonstrate the in vivo applicability of this MRI technique to experimental mouse models of multiple sclerosis. Copyright © 2015 John Wiley & Sons, Ltd.